Aging, Asset Allocation, and Costs : Evidence for the Pension Fund Industry in Switzerland - Weber, Rene (IMF Working Papers; Working Paper ;, 2007)
This paper focuses on the nexus between pension funds' balance sheet liabilities, reflecting their age profile and payments obligations, and the investment behavior and costs of these funds. The context of the analysis is the stringent regulatory framework and the highly fragmented and heterogeneous pension fund landscape in Switzerland. Detailed data from the Swiss Pension Statistic are analyzed using multivariate OLS-regressions. The evidence shows that a younger age structure and lower short-term benefits payouts are related to a higher share of equities and lower real estate holdings. Legal form, pension plan type, and size are important for administrative costs. The findings support the view that aging may lead to increased risk aversion and thus to a lower engagement of institutional investors in equities.